Human Resource Management in Islamic Boarding Schools: A Case Study at Pondok Pesantren Imam Muslim, North Sumatra - Fitria, Norma; Riduwan, Muhammad; Solehan (Nizham Jurnal Studi Keislaman, 2025)
This study aims to examine the implementation of Human Resource Management (HRM) in improving the quality of educators and education personnel at Pondok Pesantren Imam Muslim. The research seeks to understand how HRM practices contribute to the enhancement of educational quality through systematic management, training, and professional development. Employing a qualitative descriptive method, the data were collected through observation, interviews, and documentation with the head of the madrasah, educators, staff, and foundation representatives. The findings reveal that HRM at Pondok Pesantren Imam Muslim is implemented through six key aspects such as planning, recruitment, selection, training and development, performance evaluation, and integration. The study found that both educators and education personnel play significant roles not only as instructors and administrators but also as moral guides and role models in nurturing students’ religious and ethical values. Effective HRM practices at Pondok Pesantren Imam Muslim contribute substantially to improving the quality of human resources, enhancing institutional performance, and promoting the development of Islamic education within a modern educational framework.